Symptom experiences and influencing factors in patients undergoing chemotherapy for gastrointestinal cancers: a qualitative study - Huang, Xiaoying; Yang, Heng; Qiao, Yanyan (Frontiers in Psychology, 2024)
Objective: To explore the symptom experiences and influencing factors of gastrointestinal(GI) cancer patients on chemotherapy(CTX) in China.Methods: Semi-structured interviews were conducted with 13 GI cancer patients undergoing CTX.Following the Colaizzi 7-step analysis method, the interview data were read carefully, meaningful statements related to the research questions were extracted, coded, collected, and described in detail, and the authenticity of the theme was verified.Results: Nine themes were grouped into two main areas including the characteristics of symptom experiences and influences on symptom experiences.The symptom experiences of patients undergoing CTX for GI cancer is poor and influenced by multiple factors. Nurses need to pay attention to the assessment and monitoring of CTX-related symptoms, improve symptom recognition, enhance doctor-patient communication and social support, explore intelligent management methods, and increase the efficiency of healthcare services to improve patients' symptom experience.